A comparison of the effectiveness of different doses of tocilizumab and sarilumab in the treatment of severe COVID-19: a natural experiment due to drug shortages. (April 2023) - Swets, Maaike C.; Moss, Rob J.; Kor, Flip; Hilarius, Doranne; Moes, Dirk Jan A.R.; Berkhout, Willemijn EM; van den Toorn, Leon M.; van den Oever, Niels C. Gritters; de Valk, Renee; Rosendaal, Frits R.; Hunfeld, Nicole; Groeneveld, Geert H.; et al.
Highlights: Interleukin-6 inhibitors are used to treat patients hospitalized with COVID-19. Due to drug shortages, different dosing regimens were used. 60-day mortality was the lowest for patients treated with 8 mg/kg tocilizumab. The 8 mg/kg dosing regimen had the lowest odds of progression to the intensive care unit or death. Abstract: Objectives: Interleukin (IL)-6 inhibitors are administered to treat patients hospitalized with COVID-19. In 2021, due to shortages, different dosing regimens of tocilizumab, and a switch to sarilumab, were consecutively implemented. Using real-world data, we compare the effectiveness of these IL-6 inhibitors. Methods: Hospitalized patients with COVID-19, treated with IL-6 inhibitors, were included in this natural experiment study. Sixty-day survival, hospital- and intensive care unit (ICU) length of stay, and progression to ICU or death were compared between 8 mg/kg tocilizumab, fixed-dose tocilizumab, low-dose tocilizumab, and fixed-dose sarilumab treatment groups. Results: A total of 5485 patients from 49 hospitals were included. After correction for confounding, increased hazard ratios (HRs) for 60-day mortality were observed for fixed-dose tocilizumab (HR 1.20, 95% confidence interval [CI] 1.04-1.39), low-dose tocilizumab (HR 1.12, 95% CI 0.97-1.31), and sarilumab (HR 1.24, 95% CI 1.08-1.42), all relative to 8 mg/kg. The 8 mg/kg dosing regimen had lower odds of progression to ICU or death. Both hospital- and ICU length of stay were shorter for low-dose tocilizumab than for the 8 mg/kg group. Conclusion: We found differences in the probability of 60-day survival and the incidence of the combined outcome of mortality or ICU admission, mostly favoring 8 mg/kg tocilizumab. Because of potential time-associated residual confounding, further clinical studies are warranted.